2021
DOI: 10.1007/s00126-021-01045-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and boron isotopic compositions of tourmaline at the Dachang Sn-polymetallic ore district in South China: Constraints on the origin and evolution of hydrothermal fluids

Abstract: The Dachang Sn-polymetallic ore district in South China is the second largest tin district in the world with a tin reserve of over one million tonnes. Zn-Cu skarn and stratiform, massive, and vein Sn-Pb-Zn ores are all present in this district. This has led to a debate as to whether the Sn orebodies were formed by Cretaceous magmatic-hydrothermal replacement or Devonian submarine exhalative-hydrothermal sedimentation. Here, we present a systematic investigation of the major, trace element, and boron isotopic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Jiang emphasized the effects of co-existing minerals that have a marked impact on REE concentrations and patterns in tourmaline, including zircon, xenotime and monazite [45]. It was verified by Zhao et al [30,46]. The recent study of Vereshchagin et al [47] confirmed that Eu 3+ and Nd 3+ occupy the 9coordinated X-site in the tourmaline structure.…”
Section: Implications For Growth History and Colour Genesismentioning
confidence: 96%
“…Jiang emphasized the effects of co-existing minerals that have a marked impact on REE concentrations and patterns in tourmaline, including zircon, xenotime and monazite [45]. It was verified by Zhao et al [30,46]. The recent study of Vereshchagin et al [47] confirmed that Eu 3+ and Nd 3+ occupy the 9coordinated X-site in the tourmaline structure.…”
Section: Implications For Growth History and Colour Genesismentioning
confidence: 96%
“…The widely developed minerals such as vesuvianite, axinite, fluorite, and tourmaline in the Dachang ore field indicate that the ore-forming fluid contained large amounts of volatiles F and B. Zhao et al [53] analyzed the trace elements B isotopes of tourmaline in the Longxianggai granitic pluton and the Dachang ore field and noted that the ore-forming fluid and volatile B were mainly from magmatic hydrothermal fluids.…”
Section: Influence Of the Volatile On Mineralizationmentioning
confidence: 99%
“…Among them, tin polymetallic ore bodies have been well studied, and much work has been conducted on the deposit geology, metallogenic age, diagenetic age, fluid inclusion, mineralogy, isotopic geochemistry, etc. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, research on the lower zinc-copper ore bodies is relatively limited.…”
Section: Introductionmentioning
confidence: 99%